Identity, community, and learning lives in the digital age - Erstad, Ola.; Sefton-Green, Julian (Cambridge : Cambridge University Press, 2013)
'Recent work on education, identity and community has expanded the intellectual boundaries of learning research. From home-based studies examining youth experiences with technology, to forms of entrepreneurial learning in informal settings, to communities of participation in the workplace, family, community, trade union and school, research has attempted to describe and theorize the meaning and nature of learning. Identity, Community, and Learning Lives in the Digital Age offers a systematic reflection on these studies, exploring how learning can be characterized across a range of'whole-life' experiences. The volume brings together hitherto discrete and competing scholarly traditions: sociocultural analyses of learning, ethnographic literacy research, geo-spatial location studies, discourse analysis, comparative anthropological studies of education research and actor network theory. The contributions are united through a focus on the ways in which learning shapes lives in a digital age'--
'Identity, Community, and Learning Lives in the Digital Age Recent work on education, identity, and community has expanded the intellectual boundaries of learning research. From home-based studies examining youth experiences with technology, to forms of ntrepreneurial learning in informal settings, to communities of participation in the workplace, family, community, trade union, and school, research has attempted to describe and theorize the meaning and nature of learning. Learning Lives offers a systematic reflection on these studies, exploring how learning can be characterized across a range of'whole-life' experiences. The volume brings together hitherto discrete and competing scholarly traditions: sociocultural analyses of learning, ethnographic literacy research, geo-spatial location studies, discourse analysis, comparative anthropological studies of education research, and actor network theory. The contributions are united through a focus on the ways in which learning shapes lives in a digital age'--
Machine generated contents note: Introduction: why learning lives? Julian Sefton-Green and Ola Erstad; Part I. Changing Approaches to Studying Learning: Identity, Policy and Social Change: 2. Tracing learning and identity across sites: tensions, connections and transformations in and between everyday and institutional practices Hans Christian Arnseth and Kenneth Arnseth; 3. Procedural methodologies and digital forms of learning Kirsten Drotner; 4. Thinking about feeling: affect across literacies and lives Jay Lemke; 5. Learning lives in second modernity Lynne Chisholm; 6. Digital dis-connect? The'digital learner' and the school Ola Erstad and Julian Sefton-Green; Part II. From Learning to Learners: Learning Lives as They are Lived: 7. Expanding the chronotypes of schooling for the promotion of students' agency Antti Rajala, Jaakko Hilppo, Lasse Lipponen and Kristiina Kumpulainen; 8. Discursive construction of learning lives for individuals and the collective Judith Green, Audra Skukauskaite and Maria Lucia Castanheira; 9. Social entrepreneurship: learning environments with exchange value Shirley Brice Heath; 10. The construction of parents as learners about pre-school children's development Helen Nixon; 11. Participant categorizations of gaming competence: Noob and Imba as learner identities Bjorn Sjoblom and Karin Aronsson; 12. Making a film-maker: four pathways across school, peer culture, and community Oystein Gilje; 13. Portrait of the artist as a younger adult: multimedia literacy and'effective surprise' Mark Evan Nelson, Glynda A. Hull and Randy Young.
Includes bibliographical references and index.
Keywords: Learning -- Social aspects; Educational sociology; Digital communications; Identity (Psychology).